2019
DOI: 10.1186/s12978-019-0727-4
|View full text |Cite
|
Sign up to set email alerts
|

Extent of induced abortions and occurrence of complications in Kinshasa, Democratic Republic of the Congo

Abstract: Background Due to a lack of relevant data on induced abortions in the Democratic Republic of the Congo (DRC) as well as the persistence of maternal deaths in the country, this study aims to analyse the extent of induced abortions and occurrence of complications in Kinshasa. Methodology This cross-sectional study was conducted with a sample of 460 women who were interviewed about their experiences as females, and provided information of 1444 women of childbearing age liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 19 publications
(12 reference statements)
1
17
0
2
Order By: Relevance
“…Yet, fear of school dropout was mentioned as a primary reason for demanding an induced abortion service among women of reproductive age in Ethiopia [ 20 , 28 ]. Similarly, studies conducted in low- and middle-income countries have consistently shown that unmarried women (single/separated/divorced/widowed) had higher odds of having an induced abortion compared with those who were married [ 15 , 29 , 30 ]. Other reasons could be difficulty in accessing contraception, not having adequate financial and social support to provide for their unborn child, and stigma related to having a child outside of wedlock have been indicated for higher odds of induced abortion among unmarried women [ 27 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, fear of school dropout was mentioned as a primary reason for demanding an induced abortion service among women of reproductive age in Ethiopia [ 20 , 28 ]. Similarly, studies conducted in low- and middle-income countries have consistently shown that unmarried women (single/separated/divorced/widowed) had higher odds of having an induced abortion compared with those who were married [ 15 , 29 , 30 ]. Other reasons could be difficulty in accessing contraception, not having adequate financial and social support to provide for their unborn child, and stigma related to having a child outside of wedlock have been indicated for higher odds of induced abortion among unmarried women [ 27 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the Democratic Republic of Congo (DRC), where legal advances in the practice of abortion are ignored by the population, and by a large majority of healthcare providers who remain committed to article 32 of the code of medical ethics which prohibits this practice unless its indication is the only way to save the life of the mother in danger, the rate of induced abortions is estimated at 55 per 1000 women of childbearing age in Kinshasa its capital [ 8 ]. Nearly half of these abortions are followed by complications that include hemorrhage, infection and traumatic injuries (genital trauma and uterine perforation).…”
Section: Introductionmentioning
confidence: 99%
“…Nearly half of these abortions are followed by complications that include hemorrhage, infection and traumatic injuries (genital trauma and uterine perforation). About 59% of women with a complication of induced abortion seek care in referral hospitals; the remainder seek care in lower level facilities, health centers and dispensaries [ 8 ]. Women admitted to referral hospitals for complications of induced abortions account for about 12.8% of all gynecological obstetrical emergencies.…”
Section: Introductionmentioning
confidence: 99%
“…In the DRC, abortion is legally restricted. As a result, clandestine abortions are common and stigmatized [ 7 , 8 ]. Our team gave strict attention to maintaining local collaboration, which is crucial in building trusting relationships and facilitating trustworthiness, particularly when researching topics that intersect with abortion [ 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…In 2016, 40,090 women and girls obtained post abortion care with 77% requiring treatment for complications in the capital city of Kinshasa alone [ 1 , 7 ]. Mortality rates for post abortion complications are as high as 37.8% (95% CI: 23.8–53.5%) [ 8 , 9 ] owing to critical gaps in community hospitals’ provision of basic delivery services and few referral services for post abortion care [ 6 , 7 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%